Application of multiple behaviour change models to identify determinants of farmers’ biosecurity attitudes and behaviours - Richens, I.F.; Houdmont, Jonathan; Wapenaar, Wendela; Shortall, Orla; Kaler, Jasmeet; O’Connor, H.; Brennan, Marnie L. (Elsevier, 2018)
It has been recognised that few cattle farmers undertake biosecurity practices on their farms. Approaches that take into consideration individuals’ preparedness for change, alongside beliefs thought to motivate the enactment of certain behaviours, may provide a framework for actuating tangible change. The aim of this study was to use a combination of behaviour change models to link beliefs with behaviour and identify possible key interventions to improve the uptake of biosecurity measures by dairy cattle farmers in Great Britain (GB). This is the first study to explore farmers’ practices and attitudes in relation to the prevention of direct (animal to animal contact); indirect (via fomites); and other biosecurity measures using a multi-theory approach. A cross-sectional study was carried out, with postal questionnaires sent to 2505 dairy cattle farmers. Questions were asked about the extent to which a host of biosecurity measures were used, the influence of various stakeholders (e.g. veterinarians, industry bodies) in informing biosecurity choices, and the perceived control farmers felt they had over biosecurity on their farms. Farmer attitudes towards biosecurity were also explored. Two behaviour change models, the Transtheoretical Model, and the Theory of Planned Behaviour, were utilised. A variety of analysis methods were used to interrogate the data, including multivariable logistic regression. A total of 908/2505 (36.2%) farmers responded, with 757 responses (30.2%) deemed eligible for inclusion. Farmers generally fell into one of two categories: those that reported not applying biosecurity measures with no intention of doing so in the future, and those that reported undertaking biosecurity measures for some time. Farmers felt that biosecurity improved cattle health and welfare, but also felt that disease was inevitable. More farmers agreed with statements relating to their ability to control, rather than prevent disease. Analysis suggested a difference between influencing beliefs and whether specific types of measure were more likely to be undertaken. For example, farmers’ beliefs about other stakeholders appeared to play a role in influencing the utilisation of measures preventing direct contact (e.g. nose to nose contact), rather than indirect contact (e.g. fomite transmission). The use of a combination of behaviour change models has identified key variables to use for interventional approaches targeted towards the different type of biosecurity measure (preventing direct or indirect transmission) to improve the uptake of biosecurity on dairy cattle farms in GB. Other industry stakeholders should be aware of these variables when working with farmers to achieve optimal cattle herd health.